Self-assessment of the engagement of students with disabilities in the school context - Ivana; Ivana; Sretenović, Ivana; Veljković, Jasna (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Student engagement in school represents the degree to which students are invested, motivated, and willing to participate in curricular and extracurricular activities at their school, which greatly influences their future academic and professional success. Objective. The aim of our research was to examine the self-assessment of the engagement of students with developmental disabilities in the school context. Methods. The research sample consisted of 148 students with developmental disabilities, of both genders (61.5% boys), with an average age of 13.9 years, attending inclusive and elementary schools for the education of students with developmental disabilities. The School Engagement Scale was used to determine engagement. Results. The main results showed that in the majority of students with developmental disabilities, behavioral and emotional engagement was at a higher level than cognitive engagement and that the level of engagement in the behavioral and cognitive components increased with age. At the same time, students who attended schools for students with developmental disabilities had statistically significantly higher scores on the cognitive engagement domain. Conclusion. Behavioral, emotional, and cognitive engagement is perceived as a potentially effective response to problems that occur in students with developmental disabilities and should be considered when preventing problematic patterns that may arise in the school context.